2004
DOI: 10.1016/j.immuni.2004.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Excess BAFF Rescues Self-Reactive B Cells from Peripheral Deletion and Allows Them to Enter Forbidden Follicular and Marginal Zone Niches

Abstract: The role of BAFF in B cell self tolerance was examined by tracking the fate of anti-HEL self-reactive B cells in BAFF transgenic mice using four different models of self-reactive B cell deletion. BAFF overexpression did not affect the development of self-reactive B cells normally deleted in the bone marrow or during the early stages of peripheral development. By contrast, self-reactive B cells normally deleted around the late T2 stage of peripheral development were rescued from deletion, matured, and colonized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
648
1
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 662 publications
(679 citation statements)
references
References 33 publications
22
648
1
8
Order By: Relevance
“…Under these conditions, self-reactive B lymphocytes would not only be exposed to higher concentrations of Ag, but also to an environment where they must compete with non-autoreactive B lymphocytes for survival factors (e.g. BAFF) and physiological niches [19][20][21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these conditions, self-reactive B lymphocytes would not only be exposed to higher concentrations of Ag, but also to an environment where they must compete with non-autoreactive B lymphocytes for survival factors (e.g. BAFF) and physiological niches [19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…Under these conditions, self-reactive B lymphocytes would not only be exposed to higher concentrations of Ag, but also to an environment where they must compete with non-autoreactive B lymphocytes for survival factors (e.g. BAFF) and physiological niches [19][20][21].To examine B-lymphocyte tolerance to b-cell Ag within an environment where self-reactive clones comprise only a minor fraction of the total repertoire, NOD.insHEL and B6.insHEL mice as well as their non-Tg littermates were lethally irradiated and reconstituted with a mixture of BM cells from IgHEL-Tg and non-Tg donors of the same genetic background. Chimeras reconstituted with IgHEL to non-Tg BM ratios of 7:3 and 1:1 for B6 and NOD background mice, respectively, had equivalent proportions of HEL-specific B lymphocytes (mostly ranging between 10 and 20%) in BM, spleen and PLN 6 wk post-reconstitution, irrespective of whether recipients expressed insHEL or were non-Tg ( Fig.…”
mentioning
confidence: 99%
“…Moreover, elevated BAFF serum levels have been found in patients with autoimmune diseases in which B cells play an important role [81,82]. Studies aimed at elucidating the mechanisms by which over expression of BAFF can result in loss of B-cell tolerance showed that BAFF over expression does not interfere with the central tolerance program in the bone marrow but rather prevents autoreactive B cells being anergized in the periphery [83]. Currently, the potential of neutralizing BAFF as a therapy for auto-immunity is being tested both in mouse and clinical settings.…”
Section: Transitional Splenic B Cellsmentioning
confidence: 99%
“…BAFF-induced autoimmunity in BAFF Tg mice appears to be highly dependent on B cells and possibly the production of autoantibodies (11). High levels of BAFF have been found in the blood of patients with autoimmune diseases, particularly SLE and SS (10,(12)(13)(14)(15). And BAFF was also found on T lymphocytes infiltrating labial salivary glands from patients with SS (16).…”
Section: Introductionmentioning
confidence: 99%